Implikasi Hukum Terhadap Kontrak Kerja Fleksibel, Antara Kesejahteraan Pekerja dan Kepentingan Bisnis - Hia, Imelda Indah Putri (Media Hukum Indonesia (MHI), 2024)
In today's workplace, flexible work arrangements have become one of the most common phenomena. This type of contracting provides a freeze for companies to adapt their workforce to market conditions, but it also often creates complex legal requirements. This article reveals the application of the law to flexible work arrangements by highlighting employee work ethics and business needs. First, an analysis will be conducted on how flexible work arrangements affect employees' work-related stress, including stress-related health problems, social stress, and economic stability. Second, an understanding of the laws of business needs, such as operational openness, cost efficiency, and market adaptability, will be discussed. Next, this article will examine the relationship between these two aspects, the importance of business ethics and employee ethics as well as the challenges that arise in achieving a balance between the two aspects mentioned above. By exploring a deeper understanding of the legal essence of flexible work contracts, this article is expected to provide guidance for policy companies, legal practitioners, and parties involved in the work environment to ensure fairness and balance between the interests of workers and business.